Language Needs and Challenges of Non-Native English-Speaking Guests - Jaja Miharja Muktahiri (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This study explores the language needs and communication challenges encountered by non-native English-speaking guests in hospitality settings. The research aims to identify common barriers, emotional impacts, coping mechanisms, and actionable solutions to enhance guest experiences and inclusivity. Research methods: A qualitative approach was employed through semi-structured interviews and surveys with 50 non-native English-speaking guests from diverse linguistic backgrounds. Participants were selected using purposive sampling to ensure diversity in nationality, age, and travel purpose. Data was analysed using thematic coding via NVivo software to extract recurring themes and insights. Results and discussion: The findings reveal that non-native speakers frequently face difficulties such as understanding accents, limited vocabulary for specific service contexts (e.g., dining or navigation), and dependence on translation apps or gestures for communication. These challenges often lead to frustration, embarrassment, or reduced satisfaction with their overall experience. Participants emphasized the importance of multilingual staff training programs, accessible written materials in multiple languages, and improved signage as practical solutions. Additionally, they highlighted the value of real-time translation tools during interactions with staff. Implications: The study underscores the critical need for tailored communication strategies within hospitality services to address language barriers effectively. Implementing these strategies can significantly improve guest satisfaction while fostering a more inclusive environment for international travellers.